Cyclical Fluctuations in Workplace Accidents - Jan Boone; Jan C. van Ours (Institute for the Study of Labor (IZA), 2002)
This paper presents a theory and an empirical investigation on cyclical fluctuations in workplace accidents. The theory is based on the idea that reporting an accident dents the reputation of a worker and raises the probability that he is fired. Therefore a country with a high or an increasing unemployment rate has a low (reported) workplace accident rate. The empirical investigation concerns workplace accidents in OECD countries. The analysis confirms that workplace accident rates are inversely related to both the level of unemployment and the change in unemployment. Furthermore, fatal accident rated do not fluctuate over the cycle. We conclude that our empirical analysis is in line with our theory: cyclical fluctuations in workplace accidents have to do with reporting behavior of workers and not with changes in workplace safety.
Keywords: J28; I31; 330; workplace accidents; unemployment; Arbeitsunfall; Arbeitslosigkeit; Zeitreihenanalyse; Schätzung; OECD-Staaten